Efektivitas Komposting Limbah Padat Serai Wangi Dengan Menggunakan EM4 dan Mikro Organisme Lokal (Nasi Basi dan Serai Wangi) - Salsabila Nur Ramadhan; Rd Halim; Fitria Eka Putri; Oka Lesmana; Fajrina Hidayati (Fakultas Kesehatan Masyarakat Universitas Andalas, 2023)
Unused citronella solid waste can disturb the view and has the potential to pollute the environment, a solution that can be done is to process citronella solid waste into compost. The purpose of this study was to determine the effectiveness of composting citronella solid waste using EM4 and local micro-organisms (stale rice and citronella). This type of experimental research and research design is a one- shot case study. By using EM4, moles of stale rice, moles of citronella and carried out 3 repetitions and obtained 9 samples. Collecting data by observing, measuring and laboratory tests. Data analysis was performed using the Kruskal Wallis test. As for the results of data analysis, namely the p value on NPK is > 0.05, then the NPK in citronella solid waste compost using EM4, MOL of stale rice and MOL of citronella there is no significant difference. Laboratory results on citronella solid waste compost with EM4, MOL of stale rice and MOL of citronella produce Nitrogen and C/N values that do not meet the requirements of SNI 19-7030-2004. Composting citronella solid waste using EM4 and Local Micro-Organisms (stale rice and citronella) is not effective because at the end of composting it produces a low Nitrogen value and a high C/N rasio